2022
DOI: 10.17344/acsi.2021.6886
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative and Antiprostate Cancer Activities of Heterocyclic Compounds Derived from Cyclohexane-1,4-dione

Abstract: 2-Amino-6-oxo-4,5,6,7-tetrahydrobenzo[b]thiophene-3-carbonitrile (3) was prepared from the reaction of cyclohexane-1,4-dione with elemental sulfur and malononitrile in 1,4-dioxane and triethylamine as catalyst. The latter compound reacted with triethyl orthoformate and either malononitrile or ethyl cyanoacetate in 1,4-dioxane in the presence of triethylamine to produce 4H-thieno[2,3-f]chromene derivatives 10a,b. In addition, fused pyran and pyridine derivatives were synthesized starting from compound 3. The cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Our previous work demonstrated that many of the synthesized compounds were useful in future drug designing. [23][24][25][26] In continuation of the previous work we are describing here a rapid and efficient preparation of a set of new benzo [d] thiazole derivatives starting from ortho-aminothiophenol that reacted with either ethyl cyanoacetate, diethylmalonate or ethyl acetoacetate. This new approach enables more rapid generation of a higher number of benzo [d]thiazole derivatives that were obtained using simple reactions using readily available reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work demonstrated that many of the synthesized compounds were useful in future drug designing. [23][24][25][26] In continuation of the previous work we are describing here a rapid and efficient preparation of a set of new benzo [d] thiazole derivatives starting from ortho-aminothiophenol that reacted with either ethyl cyanoacetate, diethylmalonate or ethyl acetoacetate. This new approach enables more rapid generation of a higher number of benzo [d]thiazole derivatives that were obtained using simple reactions using readily available reagents.…”
Section: Introductionmentioning
confidence: 99%
“…1 Moreover, heterocyclic compounds have been reported as a significant class of organic molecules where they are the main scaffolds for the variety of bioactive compounds. 27,28 So, depending on our experience in the synthesis of the thaizole derivatives, 29 we aim to synthesize series of coumarins bearing thiazole nucleus. Thus, the de-rivatives of thiosemicarbazone will be subjected to ring closure by ethyl chloroacetate, chloroacetone and phenacyl bromide in the hope of obtaining potent antimicrobial thiazole derivatives.…”
Section: Introductionmentioning
confidence: 99%